Experimental and pore-level numerical investigation of water evaporation in gas diffusion layers of polymer electrolyte fuel cells. (December 2017) - Safi, Mohammad Amin; Prasianakis, Nikolaos I.; Mantzaras, John; Lamibrac, Adrien; Büchi, Felix N.
Highlights: Micro-pore level simulations for evaporation over a full-size partially saturated 3D porous medium. Results are compared with experimental data for water evaporation under different gas flow rates. Key transport mechanisms controlling the evaporation in a real porous medium are inspected. Effect of evaporation induced velocities on the flow pattern inside porous media is investigated. Abstract: The liquid water generated by the electrochemical reaction in a polymer electrolyte fuel cell (PEFC) can greatly affect the cell performance and/or efficiency. Phase change of the water due to evaporation is therefore an important process in understanding the water and flow behavior in the porous gas diffusion layers (GDLs) of PEFCs. In this work a 3D lattice Boltzmann (LB) methodology is adopted to model the flow and mass diffusion in a binary air/water mixture. A modeling framework is designed so as to focus on the understanding of the phase change processes of stationary water inside a GDL with a thickness less than 0.25 mm. Consistent models are employed to simulate evaporation at pore scale and on the irregular water-gas interface. The numerically obtained evaporation fluxes are compared against experimental data for the exact same 3D porous GDL sample. The pore-scale simulations are first shown to be in good agreement with the measurements for global evaporation rates in GDLs. Numerical simulations are then performed inside and outside the GDL to investigate the physics of evaporation, including the interaction between the diffusion at pore scale and the external convection in the channel of the PEFC. The role of evaporation-induced flows is finally studied by comparing the computed magnitudes of the vertical velocities obtained with and without inclusion of evaporation.